Heterotopic pregnancy with molar changes - Satia, Meena N.; More, Vibha; Ganapathi, Trupthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Trophoblastic disease of pregnancy is also called as gestational trophoblastic disease (GTD), a rare group of tumors that involves abnormal proliferation of the trophoblastic cells. GTD is generally benign but sometimes can be malignant due to its marked penetration into and destruction of myometrium as well as its ability to metastasize hence the groups of tumors are referred to as gestational trophoblastic neoplasm (GTN). These are among the rare tumors that can be cured even in the presence of widespread dissemination. Present study is a case of intrauterine partial mole with ectopic pregnancy in the right adnexa with vesicular changes, a rare entity in obstetrics.